2000
DOI: 10.1002/1097-0045(2000)45:9+<34::aid-pros8>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ?1-adrenoceptor antagonists on cultured prostatic smooth muscle cells

Abstract: BACKGROUND α1‐adrenoceptor (α1‐AR) antagonists, used to relieve the lower tract urinary symptoms (LUTS) in benign prostate hyperplasia (BPH) patients, are thought to act in inhibiting the contraction of stromal smooth muscle. An attempt was made using new technology to visualize and quantify the effect of α1‐AR antagonists in a cell culture model of prostatic smooth muscle cells (SMC). METHODS Prostatic smooth muscle cells cultured from human prostate tissue were treated with α1‐AR agonists and antagonists. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Spontaneous elevations of calcium and spontaneous contractions have been shown previously in HCPSC 15,16. Although Boesch et al 16 report that the number of cells exhibiting spontaneous contractions is significantly elevated by the α‐adrenoceptor agonist phenylephrine, in our studies the non‐selective adrenoceptor agonist, noradrenaline, had no effect on peaking activity.…”
Section: Discussionsupporting
confidence: 55%
“…Spontaneous elevations of calcium and spontaneous contractions have been shown previously in HCPSC 15,16. Although Boesch et al 16 report that the number of cells exhibiting spontaneous contractions is significantly elevated by the α‐adrenoceptor agonist phenylephrine, in our studies the non‐selective adrenoceptor agonist, noradrenaline, had no effect on peaking activity.…”
Section: Discussionsupporting
confidence: 55%
“…Studies from this and other laboratories have shown that human cultured prostatic stromal cells make a reasonably good model of human prostate contractility since they respond to phenylephrine with a 1 -adrenoceptor antagonist-sensitive contractions [23][24][25]. These contractions and corresponding elevations of intracellular Ca 2þ are also sensitive to nifedipine [24].…”
Section: Discussionmentioning
confidence: 83%
“…Several studies have shown that freshly dissociated prostatic myocytes and cultured prostatic stromal cells exhibit some of the same characteristics as preparations of intact prostate. Specifically, they respond to phenylephrine with contractions that are blocked by α 1 ‐adrenoceptor antagonists (Boesch et al ., 2000; Corvin et al ., 1998; Eckert et al ., 1995), and also with an increase in [Ca 2+ ] i (Eckert et al ., 1995). Previous work from our laboratory has implicated PKC activation in the phorbol ester‐mediated contractility of HCPSC (Haynes et al ., 2002), however the role of PKC in the α 1 ‐adrenoceptor‐mediated contractility of HCPSC remains equivocal (Eckert et al ., 1995; Marshall et al ., 1999).…”
Section: Introductionmentioning
confidence: 99%